Ground-state charge-transfer interactions in donor:acceptor pairs of organic semiconductors – a spectroscopic study of two representative systems. Issue 31 (31st July 2019) - Duva, Giuliano; Beyer, Paul; Scholz, Reinhard; Belova, Valentina; Opitz, Andreas; Hinderhofer, Alexander; Gerlach, Alexander; Schreiber, Frank
Abstract : Nature of ground-state charge-transfer quantified by means of FTIR spectroscopy for the D:A pairs DIP:F6TCNQ and P3HT:F6TCNQ. Abstract : We investigate blended donor:acceptor (D:A) thin films of the two donors diindenoperylene (DIP) and poly(3-hexylthiophene) (P3HT) mixed with the strong acceptor 1, 3, 4, 5, 7, 8-hexafluorotetracyanonaphthoquinodimethane (F6 TCNNQ) using Polarization-Modulation Infrared Reflection-Absorption Spectroscopy (PMIRRAS). For DIP:F6 TCNNQ thin films we first carry out a comprehensive study of the structure as a function of the D : A mixing ratio, which guides the analysis of the PMIRRAS spectra. In particular, from the red-shift of the nitrile (CN) stretching of F6 TCNNQ in the different mixtures with DIP, we quantify the average ground-state charge-transfer (GS-CT) to be ρ avg = (0.84 ± 0.04) e . The PMIRRAS data for P3HT:F6 TCNNQ blended films reveal nearly the same shift of the CT-affected CN stretching peak for this system. This points towards a very similar CT strength for the two systems. We extend the analysis to the relative intensity of the CN to the CC stretching modes of F6 TCNNQ in the mixtures with DIP and P3HT, respectively, and support it with DFT calculations for the isolated F6 TCNNQ. Such comparison allows to identify the vibrational signatures of the acceptor mono-anion in P3HT:F6 TCNNQ, thus indicating a much stronger, integer CT-type interactions for this system, in agreement with available optical spectroscopy data. Our findings stress the importance of a simultaneous analysis of CN and CC stretching vibrations in F6 TCNNQ, or similar quinoid systems, for a reliable picture of the nature of GS-CT interactions.